Formulation of Orally Disintegrating Tablet from Nifedipin-β-siklodekstrin Inclusion Complex using Kneading Method - Nur Aini Purnamasari; Pratama Anggi Saputra (Faculty of Pharmacy, Universitas Gadjah Mada, 2019)
Nifedipine is widely used for managing hypertension. The challenges of developing nifedipine oral preparation are its low solubility and unpleasant taste. The purpose of developing the Oral Disintegrating Tablet (ODT) dosage form from the Nifedipine-β-cyclodextrin inclusion complex is to increase the solubility of nifedipine and mask the unpleasant taste of the drug. Specific target: use of a superdisintegrant combination to increase the solubility of nifedipine and mask the bitter taste. The method used in the formation of Nifedipine inclusion complex with β-cyclodextrin was kneading method. Making ODT was done by direct pressing method. Characterization of nifedipine-β-cyclodextrin inclusion complex was analyzed by FTIR and DSC. ODT was tested for the physical properties of the tablet and its solution. Test results for ODT physical properties were analyzed and compared with the literature. Data obtained from the dissolution test results calculated the concentration of the active substance dissolved at 20 minutes (Q20). The results showed that the formation of the Nifedipine-β-cyclodextrin inclusion complex increased solubility and masked the bitter taste. The combination of superdisintegrant Ac-Di-Sol-Crosspovidon accelerated the disintegration and dissolution time and improve the taste of Nifedipine ODT.